Er3+ and K0.5Na0.5NbO3 modified Ba0.85Ca0.15Ti0.9Zr0.1O3: Novel translucent ceramics with reversible photochromism. Issue 18 (15th December 2019) - Liu, Chunwen; Xu, Jie; Wang, Quanlin; Lin, Jinfeng; Wu, Xiao; Lin, Cong; Zheng, Xinghua; Lin, Tengfei
Abstract: Er 3+ -doped xK0.5 Na0.5 NbO3 -(1-x)Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 (x = 0.04, 0.05, 0.06 and 0.07) translucent ceramics have been first prepared by conventional pressureless sintering. Owing to the effective suppression of grain growth induced by both Er 3+ and K0.5 Na0.5 NbO3, the ceramics possess dense and fine-grained microstructure. The XRD patterns demonstrate cubic-like phase structure with minimal optical anisotropy. The ceramics perform good photochormic (PC) properties under 407-nm light irradiation and superior reproducibility after heat treatment (200 °C, 5 min). And PC reaction is responsible for coloration and decoloration processes. The up-conversion photoluminescence before and after irradiation have been studied. With increasing the K0.5 Na0.5 NbO3 content or elevating the sintering temperature of the ceramics, the luminescent quenching degree (ΔRt ) gradually increases. The color centers induced by irradiation can be reversibly created or eliminated, resulting in invertible luminescent modulations. This work can guide other multifunctional PC transparent ferroelectric materials for optoelectronic applications.